Praktek Pengalihan Tanah Secara Nominee Dalam Mewujudkan Ketahanan Pangan Di Provinsi Banten - Suhadi, Aris; Muslih, Muhamad; Gunawati, Anne (MADINAH, 2020)
A nominee or trustee agreement is an agreement that uses power, namely an agreement that uses the name of an Indonesian citizen and the Indonesian citizen submits a power of attorney to a foreign citizen to be free to carry out legal actions on the land they own. The nominee agreement is often also referred to as a representative or borrowing a name based on a statement or power of attorney made by both parties, a foreigner borrows the name of an Indonesian citizen to include his name as the owner of the land on the certificate, but then an Indonesian citizen based on the statement deed he makes denies that the actual owner is a foreign citizen as the party who issued the money for the purchase of the land and the control is carried out or represented by the foreign citizen. The validity and binding power of the nominee agreement cannot be separated from the provisions of Article 1320 and Article 1338 of the Civil Code. If the nominee agreement has taken into account and fulfilled the legal requirements of the agreement according to Article 1320 of the Civil Code and based on the provisions of Article 1338 of the Civil Code, then the nominee agreement has binding force for the parties. Based on the principle of pacta sund servanda that the agreement made by the parties, including the nominee agreement has binding force as law for those who make it. This study describes the practice of land transfer by nominee in realizing food security in the province of Banten. This research is also to find out, examine and develop alternative policies related to efforts to optimize the potential of agricultural land used for food utilization. The long-term goal to be achieved from this research is that this research aims to seek land management and use to support food security in Banten and national food security. Food products in Banten can not only meet the needs of their own region, but can also meet the needs of National Food and even for export commodities to foreign countries. The specific target to be achieved from this research is to seek to know the Nominee Land Transfer Practices in Banten Province, both in terms of the quantity of practice and from local government regulations in dealing with these problems. This research uses Sociological Normative and Juridical Normative legal research methods. This research is descriptive analytical and uses primary data sources and secondary data sources. Descriptive in this research in the form of a description of the situation, conditions, circumstances, and the reality that exists then analyzed what the problem is in order to find a solution to the problem. Sources of data used in this study were obtained from Library Research (Library Research). Normative Jurisdiction in this study is a discussion of several laws and regulations made by the government that are enforced. Sociological Normative Research on law constructs law as a system of laws and regulations that have existed so far and then constructed in a society's behavior.